The relationship among Turkish EFL learners' willingness to communicate in English, self-efficacy perceptions and linguistic self-confidence - İsmail Saka; Ali Merç (Literacy Trek, 2021)
The objective of this study was to investigate the level of English preparation class students' WTC in English, their self-efficacy perceptions, and their linguistic self-confidence. This study also aimed to explore the possible correlation among these variables. Eighty-four Turkish EFL learners studying at compulsory English preparatory classes at Yozgat Bozok University in Turkey participated in the study. A mixed-method research design was adopted. The quantitative data were collected through 4 five-point Likert-type scales: the WTC scale, the Communication Anxiety Scale, and the Perceived Communication Competence Scale, and the Self-Efficacy Scale. The qualitative data involved semi-structured interviews conducted with 30 of the students. Both qualitative and quantitative data revealed that students were somewhat willing to communicate, they perceived themselves somewhat confident in English, they did not experience much communication anxiety, and they had a medium level of perceived self-efficacy in English. Correlation analyses showed that there was a negative relationship between communication anxiety and other three affective variables, namely, perceived communication competence, willingness to communicate and self-efficacy. The findings further revealed a positive relationship between students' willingness to communicate and other variables such as their perceived communication competence, self-efficacy, and linguistic self-confidence. A positive relationship was also observed between students' self-efficacy and their perceived communication competence and linguistic self-confidence. The implications of the study were discussed and some recommendations for further studies were made.